1999
DOI: 10.1103/physrevlett.83.2120
|View full text |Cite
|
Sign up to set email alerts
|

Domain Walls in Supersymmetric QCD: From Weak to Strong Coupling

Abstract: We consider domain walls that appear in supersymmetric QCD with N f , N c massive flavors. In particular, for 2N f , N c we explicitly construct the domain walls that interpolate between vacua labeled by i and i 1 N f . We show that these solutions are Bogomol'nyi-Prasad-Sommerfield saturated for any value of the mass of the matter fields. This fact allows us to evaluate the large mass limit of these domain walls. We comment on the relevance of these solutions for supersymmetric gluodynamics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…This is recognizable as a spinor analogue of the unbroken supercharge within the S 3 model. If we now drop the translational zero modes, and restrict Q α to the reduced moduli space, with x i = {ξ 0 , φ 0 }, then we discover that there is a second unbroken spinor supercharge, existing by virtue of the complex structure J associated with M = S 2 , introduced earlier in (16). We can then form a complex spinor charge…”
Section: • the Decoupling Regimementioning
confidence: 91%
See 1 more Smart Citation
“…This is recognizable as a spinor analogue of the unbroken supercharge within the S 3 model. If we now drop the translational zero modes, and restrict Q α to the reduced moduli space, with x i = {ξ 0 , φ 0 }, then we discover that there is a second unbroken spinor supercharge, existing by virtue of the complex structure J associated with M = S 2 , introduced earlier in (16). We can then form a complex spinor charge…”
Section: • the Decoupling Regimementioning
confidence: 91%
“…The corresponding central charge is present in the superalgebra [9] and such solitons are 1/2-BPS saturated. In previous work [10], we studied the BPS wall spectrum in this theory, following earlier work on BPS walls in other variants of N= 1 SQCD [9,[11][12][13][14][15][16][17]. The vacuum structure is illustrated in the plane of the superpotential in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there are no massless excitations on the wall worldvolume, other than the translational modes. Numerical analysis in [15][16][17]19] , then additional solutions will arise in pairs by permutation of the fields. Perturbative analysis indicates that there are at most four trajectories emanating from each vacuum, and an analysis along the lines of [38] demonstrates that only two of these interpolate to the second vacuum providing true wall configurations.…”
Section: Breaking the Flavor Symmetry And Nmentioning
confidence: 99%
“…[10]. A couple of years ago, two of us [12] analyzed the case of N f = 1 flavour. We found that there were BPS-saturated solutions for any value of the mass parameter m. This can be seen in Fig.…”
Section: Equal Windingsmentioning
confidence: 99%